Influence of different BFO filler content on microwave absorption performances in BiFeO3/epoxy resin composites - Rusly S.N.A.; Ismail I.; Matori K.A.; Abbas Z.; Shaari A.H.; Awang Z.; Ibrahim I.R.; Idris F.M.; Mohd Zaid M.H.; Mahmood M.K.A.; Hasan I.H. (Elsevier Ltd, 2024)
Multiferroic BiFeO3 (BFO) has garnered interest in recent years due to its magneto-electric coupling between ferroelectric and magnetic ordering. This unique property offers some advantages when applied as electromagnetic (EM) wave absorbers. In work reported here, the microwave absorption properties of multiferroic BFO/epoxy resin composites with different weight percentage (wt%) of BFO fillers of various thicknesses were investigated. The BFO powders were synthesized using high energy ball milling (HEBM) and sintered at 775 °C in a furnace with an ambient air condition. The sintered BFO powders with different weight ratios (50 wt%, 60 wt% and 70 wt%) were mixed with epoxy resin as a matrix to form a composite with thicknesses of 1, 2 and 3 mm. Phase identification, grain size and morphology, magnetic and microwave absorption properties of prepared samples were characterized. The absorption performances of samples were measured in the frequency range of 8–18 GHz. As a result, the compressed BFO powders and BFO/epoxy resin composites with 50–70 wt% BFO filler showed dual-band microwave absorption resonance behavior. The best performances were demonstrated by a 3 mm thick BFO70 composite sample which exhibited a primary reflection loss (RL1) of −26.0 dB at 9.1 GHz and a secondary reflection loss (RL2) of −40.5 dB at 11.3 GHz, along with an associated −10 dB bandwidth of 1.31 GHz. The minimum reflection loss (RL) peaks were shifted to a lower frequency as the thicknesses were increased due to theλ4 condition. Theoretical studies on the absorbing wave mechanism reveal a unique combination of dielectric loss relaxations and antiferromagnetic resonance effects in the BFO absorbers.